The role of human rhinovirus in COPD exacerbations in Abu Dhabi: molecular epidemiology and clinical significance - Ahmad R. Alsayed; Anas Abed; Heba A. Khader; Luai Hasoun; Mohammed Al Maqbali; Mahmoud J. Al Shawabkeh (Libyan Journal of Medicine)
This study aimed to describe the molecular epidemiology and seasonality of human rhinovirus (HRV) in chronic obstructive pulmonary disease (COPD) and its association with COPD exacerbations in Abu Dhabi, the United Arab Emirates (UAE). Sputum specimens were collected for analysis from all COPD patients who visited a medical center from November 2021 to October 2022. The real-time quantitative polymerase chain reaction (qPCR) test was used to detect HRV. Of the 78 COPD patients included in the study, 58 (74%) patients presented with one or more exacerbation episodes. The incidence of COPD exacerbation peaked over the winter and substantially decreased during the summer. HRV positivity in patients during exacerbation (E1) was 11/58 (19%) and 15/58 (26%) two weeks after the exacerbation episode (E2). There was no significant difference in the HRV load in these patients. No statistically significant difference was observed in the detection of HRV during exacerbation compared to patients with stable COPD. This is the first study to assess the association between HRV detection by qPCR and COPD exacerbations in the UAE. The high sensitivity of the detection technology helped collect reliable epidemiologic data. Few studies have provided similar Middle East data. This study’s pattern of COPD exacerbations and HRV detection parallels that of temperate countries. This information can help with future, more extensive surveillance of respiratory viruses in the UAE and the Middle East and their association with COPD exacerbations.